The Design of A Productive Landscape Barcelona Tres Turons Park A Case Study - Pellitero, Ana Moya; Canbay Türkyılmaz, Çiğdem; Eliziario, Josue Silva; TÜRKYILMAZ, EMRAH (My University, 2009)
Urban parks can be the future green engines of a self-sufficient urban environment. They may become a productive landscape that merges nature, with a resource-efficient milieu, and a platform for ecological awareness and education. This agro-ecosystem sustains space and the surrounded neighborhoods, with community supported gardening and urban farming, integrating the production of renewable energies, natural water purification and waste management. Tres Turons Park is a strategic green space in the northern part of the city of Barcelona, Spain. The Modification of the Metropolitan Master Plan, approved in January 2009, consolidates the space for an urban public park. This paper evaluates how to design a community self-organized productive landscape in Tres Turons Park, presenting the design methodology and analyzing the results of the workshop taken place at the Faculty of Architecture of Barcelona (UPC), on July 2009, with an international team of students, and professional guests.
Keywords: sustainability; self-organization; urban farming; renewable energies; urban park; landscape design; education